Rap-agencia frente a la narcoviolencia. Análisis crítico del discurso de canciones de los raperos de García, Nuevo León, México (2021)
The objective of this article is to show how rappers from a municipality in the metropolitan periphery of Monterrey, México, confront the violence derived from the drug war through their songs. The methodology used, in addition to ethnography and participant observation, is mainly based on Critical Discourse Analysis of rappers’ rhymes, with an adaptation of Bonet’s (2012) proposal used by Araiza and González (2016), where the following are analyzed: 1) the author's position, 2) communicative interaction, 3) individuals and agencies, 4) interdiscursivity and 5) power relations. The analysis showed that rappers build their experiences using rap as a cultural resource and developing their creative agency to confront the violence derived from the drug war. The characteristics found in their lyrics are the following: 1) they avoid direct drug-related topics; 2) they slightly deal with aspects of the violence derived from the drug war; 3) they expose and/or propose alternatives to confront violence; 4) they try to raise awareness among listeners through their lyrics, that is, they rap to narrate an experience to generate a change.